2016
DOI: 10.1063/1674-0068/29/cjcp1602025
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Evaluation of Merged Pharmacophore Based on Peroxisome Proliferator Receptor-Alpha Agonists

Abstract: Pharmacophore is a commonly used method for molecular simulation, including ligand-based pharmacophore (LBP) and structure-based pharmacophore (SBP). LBP can be utilized to identify active compounds usual with lower accuracy, and SBP is able to use for distinguishing active compounds from inactive compounds with frequently higher missing rates. Merged pharmacophore (MP) is presented to integrate advantages and avoid shortcomings of LBP and SBP. In this work, LBP and SBP models were constructed for the study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…–CDOCKER ENERGY (kcal/mol) was the scoring function of CDOCKER algorithm, which represented the energy of the ligand–receptor complexes [35]. Fifty percent of –CDOCKER ENERGY for three crystal structures were regarded as the threshold for screening the potential ACE inhibitory oligopeptides [36,37]. …”
Section: Resultsmentioning
confidence: 99%
“…–CDOCKER ENERGY (kcal/mol) was the scoring function of CDOCKER algorithm, which represented the energy of the ligand–receptor complexes [35]. Fifty percent of –CDOCKER ENERGY for three crystal structures were regarded as the threshold for screening the potential ACE inhibitory oligopeptides [36,37]. …”
Section: Resultsmentioning
confidence: 99%
“…Null Cost of ten hypotheses was 228.61, and △cost was difference value between Null Cost minus Total Cost of each hypothesis. The △cost value of ten hypotheses greater than 60 indicated that there is generally a high probability and low contingency of models 31 . From the Table 1, correlation values between predicted and experimental activity of training set for pharmacophore models were greater than 0.8, which indicated pharmacophore models had better ability to predict activity of compounds 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The △cost value of ten hypotheses greater than 60 indicated that there is generally a high probability and low contingency of models 31 . From the Table 1, correlation values between predicted and experimental activity of training set for pharmacophore models were greater than 0.8, which indicated pharmacophore models had better ability to predict activity of compounds 31 . Then testing set was used to compute external indexes of the pharmacophore models in order to analyze the capabilities of identifying active compounds from non-active compounds and distinguishing the higher activity compounds from lower activity compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Binding sites of MAPK14 and MMP9 were identified based on initial ligands with RMSD less than 2.00Å during CDOCKER process (Table S5). The compounds with -CDOCKER INTERACTION ENERGY higher than initial ligands were regarded as the potential active compounds (12). Combining the scores of pharmacophore and molecular docking, potential active compounds were identified for MAPK14 and MMP9 (Table S6).…”
Section: (Page Number Not For Citation Purpose)mentioning
confidence: 99%